Off-line method for evaluating gas washing resistance of catalyst layer
By simulating the bubble erosion phenomenon in electrolytic water, the catalytic layer is immersed in hydrogen peroxide solution, which solves the problem of time-consuming, high cost and inability to directly observe the changes in the catalytic layer structure in the prior art, and achieves a fast and low-cost catalytic layer Evaluation of gas erosion resistance.
Patent Information
- Application Number
- CN202411651152.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art uses time and cost to evaluate the catalytic layer's structural changes under gas erosion.
By simulating the bubble erosion phenomenon in the actual electrolytic environment, the catalytic layer is immersed in hydrogen peroxide solution, the generation and desorption process of bubbles on the surface of the catalytic layer are observed, and the density and size of the bubbles are recorded, and finally through scanning electron microscope or optical microscope Observe the integrity of the surface of the catalytic layer.
The structural stability of the catalytic layer is achieved quickly and the evolution of the catalytic layer under gas erosion can be directly observed, reducing testing costs and time, and helping developers quickly screen the catalytic layer and optimize its structure.
Smart Images

Figure CN119492645A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production by electrolysis of water, and in particular relates to an off-line method for evaluating the gas scouring resistance of a catalyst layer. Background Art
[0002] Proton exchange membrane (PEM) water electrolysis hydrogen production technology is an electrochemical technology that drives the water splitting reaction by applying an external voltage to decompose water molecules into hydrogen and oxygen. This technology can produce high-purity hydrogen, can be used in combination with renewable energy (such as wind energy and solar energy), can quickly respond to changes in grid demand, and is a clean way of energy conversion. With the advancement of technology, this hydrogen production method is expected to play an important role in the field of hydrogen energy.
[0003] Membrane electrode (MEA) is a key component in the electrolytic water hydrogen production system, which consists of a proton exchange membrane, a catalyst layer and a porous transport layer. Among them, the catalyst layer is the place where the electrochemical reaction occurs. It accelerates the water decomposition reaction by providing a highly active catalyst, improves the reaction rate and energy conversion efficiency, and the porous structure of the catalyst layer can improve the mass transfer efficiency and gas isolation effect, which is the decisive factor in achieving high-performance and long-life electrolytic water hydrogen production.
[0004] During the water electrolysis process, oxygen is generated in the anode side catalyst layer and hydrogen is generated in the cathode catalyst layer. These gases are generated on the catalyst layer surface and gradually form bubbles. With the generation and desorption of high-frequency bubbles, periodic mechanical stress will be generated on the catalyst layer surface. This stress will act on the catalyst layer for a long time, which will cause the catalyst to fall off, reduce active sites, destroy the catalyst layer structure, and cause holes, cracks, and even fall off, which will affect the performance and life of the catalyst layer. Therefore, the gas erosion resistance of the catalyst layer is directly related to the durability and service life of the water electrolysis equipment. Good gas erosion resistance can help the catalyst layer maintain its structural integrity, extend the service life of the water electrolysis device, and reduce the maintenance and replacement frequency.
[0005] The conventional method for evaluating the gas erosion resistance of the catalyst layer is to assemble the electrolytic cell and conduct an online water electrolysis durability test, then disassemble the electrolytic cell, remove the membrane electrode, and observe the structural stability of the catalyst layer. This method is not only time-consuming and costly, but also unable to directly observe the intermediate process of the catalyst layer being eroded by gas. At the same time, after a long period of operation of the membrane electrode, the catalyst layer will adhere to the PTL or GDL, making it difficult to remove the catalyst layer completely.
[0006] The invention patent with application number 202111336317.9 discloses a method for measuring the mechanical strength of the membrane electrode catalyst layer. This method uses an adhesive film to attach to the catalyst layer and then tear the film with external force to test the area of the catalyst layer remaining on the adhesive film to evaluate the peel strength of the catalyst layer. This method is simple to operate, but it is only suitable for evaluating the mechanical strength of the catalyst layer. It is not close to the actual working environment of water electrolysis and cannot be used to evaluate the structural stability of the water electrolysis catalyst layer under gas erosion, which has limitations. Summary of the invention
[0007] The purpose of the present invention is to address the shortcomings of conventional electrolytic water durability test for evaluating the mechanical stability of the catalyst layer, which is time-consuming, costly, and unable to directly observe the structural changes of the catalyst layer under gas scouring, and propose an offline method for evaluating the gas scouring resistance of the catalyst layer. By simulating the bubble scouring phenomenon in an actual electrolysis environment, the present invention can not only quickly evaluate the structural stability of the catalyst layer, but also directly observe the evolution of the catalyst layer structure under gas scouring, which is conducive to developers to quickly screen the catalyst layer and deeply understand the microscopic mechanism of the influence of gas scouring on the membrane electrode structure, and provide a reliable basis for its performance in practical applications.
[0008] To achieve the above technical objectives, the technical solution adopted in the embodiment of the present invention is: an offline method for evaluating the gas scouring resistance of a catalyst layer, comprising the following steps:
[0009] Step S1, mixing the catalyst, dispersant and ion exchange resin solution uniformly to form a catalyst slurry;
[0010] Step S2, coating the catalyst slurry on the substrate, and drying at 60-80° C. to form a catalyst layer;
[0011] Step S3, immersing the substrate coated with the catalyst layer in a hydrogen peroxide solution, controlling the immersion time, temperature and concentration of the hydrogen peroxide solution to simulate different degrees of bubble scouring, observing the generation and desorption process of bubbles on the surface of the catalyst layer, and recording the density and size of the bubbles;
[0012] Step S4: After the test, rinse the surface of the catalyst layer with ultrapure water, let it stand and dry at room temperature, observe the integrity of the catalyst layer surface, and assemble the catalyst layer into a single water electrolysis cell for performance testing to evaluate the degree of structural damage.
[0013] Further, in step S1, the catalyst includes a platinum-based catalyst and an iridium-based catalyst;
[0014] The ion exchange resin solution is a cation exchange resin solution.
[0015] Further, in step S2, the coating method includes one or more of spraying, blade coating, slit extrusion coating, inkjet printing and laser printing;
[0016] The substrate comprises one of a polytetrafluoroethylene membrane, a polyimide membrane, a proton exchange membrane, an anion exchange membrane, carbon paper and titanium felt.
[0017] Further, in step S3, the concentration of the hydrogen peroxide solution is 0.5-30%;
[0018] The soaking time is 1-100h, and the soaking temperature is 20-80℃.
[0019] Furthermore, in step S4, the integrity of the catalyst layer surface is detected by using a scanning electron microscope or an optical microscope to observe whether there is damage including holes, cracks or peeling on the catalyst layer surface.
[0020] The technical solution provided by the embodiment of the present invention has the following beneficial effects:
[0021] The present invention immerses the catalyst layer in a hydrogen peroxide (H2O2) solution of a certain concentration, utilizes the principle that the catalyst catalyzes the decomposition of hydrogen peroxide into water and oxygen, and generates a large number of bubbles on the surface of the catalyst layer to simulate the bubble scouring effect during the operation of an actual electrolytic cell, and is used for offline testing of the ability of the internal structure of the catalyst layer to resist bubble scouring.
[0022] The conventional method of conducting an online durability test on water electrolysis by assembling an electrolytic cell, then disassembling the electrolytic cell, removing the membrane electrode, and observing the stability of the catalyst layer structure is not only time-consuming and costly, but also unable to directly observe the intermediate processes of the catalyst layer.
[0023] The present invention simulates the bubble scouring phenomenon in an actual electrolysis environment, which is not only convenient to operate, saves time, reduces evaluation costs, and quickly evaluates the structural stability of the catalyst layer, but also can directly observe the evolution process of the catalyst layer structure under gas scouring, which is beneficial for developers to quickly screen the catalyst layer and optimize the catalyst layer structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1a This is the gas flushing phenomenon during the actual immersion treatment process of Example 2.
[0025] Figure 1b yes Figure 1a A magnified view of the gas flushing phenomenon.
[0026] Figure 2a This is an optical microscope photograph of the catalytic layer of Example 2 before immersion treatment.
[0027] Figure 2b This is an optical microscope photograph of the catalytic layer of Example 2 after immersion treatment.
[0028] Figure 3The electrolysis curves of Examples 1 and 2 are compared with those of Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] Example 1
[0031] An off-line method for evaluating the gas scouring resistance of a catalyst layer comprises the following steps:
[0032] Step S1: 1 g of 50% Pt / C catalyst, 5 g of ultrapure water, 5 g of n-propanol and 2 g of Aquivion D72 resin solution were mixed to form a catalyst slurry, and then the catalyst slurry was coated on a tetrafluoroethylene substrate and dried at 60°C to form a catalytic layer. The coated platinum loading was 0.5 mg / cm 2 ;
[0033] Step S2, using tape to stick the catalyst layer to the bottom of the glass container, pouring in a 20% H2O2 solution, soaking at 50°C for 0.5 hours, observing the generation and desorption of bubbles on the catalyst layer surface during the soaking process, and recording the density and size of the bubbles;
[0034] Step S3: After the immersion is completed, the surface of the catalyst layer is rinsed with ultrapure water and allowed to stand and dry at room temperature;
[0035] Step S4, observing the integrity of the catalyst layer surface, and assembling the catalyst layer into a single water electrolysis cell for performance testing to evaluate the degree of structural damage.
[0036] Example 2
[0037] An off-line method for evaluating the gas scouring resistance of a catalyst layer comprises the following steps:
[0038] Step S1: 1 g of 50% PtCo / C catalyst, 7 g of ultrapure water, 3 g of isopropanol and 3 g of Aquivion D79 resin solution were mixed to form a catalyst slurry, and then the catalyst slurry was coated on a proton exchange membrane substrate and dried at 65°C to form a catalytic layer. The coated platinum loading was 0.3 mg / cm 2 ;
[0039] Step S2, using tape to stick the catalyst layer to the bottom of the glass container, pouring in a 20% H2O2 solution, soaking at 50°C for 0.5 hours, observing the generation and desorption of bubbles on the catalyst layer surface during the soaking process, and recording the density and size of the bubbles;
[0040] Step S3: After the immersion is completed, the surface of the catalyst layer is rinsed with ultrapure water and allowed to stand and dry at room temperature;
[0041] Step S4, observing the integrity of the catalyst layer surface, and assembling the catalyst layer into a single water electrolysis cell for performance testing to evaluate the degree of structural damage.
[0042] Example 3
[0043] An off-line method for evaluating the gas scouring resistance of a catalyst layer comprises the following steps:
[0044] Step S1: 1 g IrO2 catalyst, 3 g ultrapure water, 7 g ethanol and 2 g Nafion D2020 resin solution were mixed to form a catalyst slurry, and then the catalyst slurry was coated on a polyimide membrane substrate and dried at 70°C to form a catalytic layer. The iridium loading was 1.5 mg / cm 2 ;
[0045] Step S2, using tape to stick the catalyst layer to the bottom of the glass container, pouring a 5% H2O2 solution into the container, soaking at 25°C for 10 hours, observing the generation and desorption of bubbles on the catalyst layer surface during the soaking process, and recording the density and size of the bubbles;
[0046] Step S3: After the immersion is completed, the surface of the catalyst layer is rinsed with ultrapure water and allowed to stand and dry at room temperature;
[0047] Step S4, observing the integrity of the catalyst layer surface, and assembling the catalyst layer into a single water electrolysis cell for performance testing to evaluate the degree of structural damage.
[0048] Example 4
[0049] An off-line method for evaluating the gas scouring resistance of a catalyst layer comprises the following steps:
[0050] Step S1: 1 g of Ir black catalyst, 5 g of ultrapure water, 5 g of n-butanol and 2 g of Nafion D2020 resin solution were mixed to form a catalyst slurry, and then the catalyst slurry was coated on a polytetrafluoroethylene substrate and dried at 80°C to form a catalyst layer. The iridium loading was 1.0 mg / cm 2 ;
[0051] Step S2, using tape to stick the catalyst layer to the bottom of the glass container, pouring a 5% H2O2 solution into the container, soaking at 25°C for 10 hours, observing the generation and desorption of bubbles on the catalyst layer surface during the soaking process, and recording the density and size of the bubbles;
[0052] Step S3: After the immersion is completed, the surface of the catalyst layer is rinsed with ultrapure water and allowed to stand and dry at room temperature;
[0053] Step S4, observing the integrity of the catalyst layer surface, and assembling the catalyst layer into a single water electrolysis cell for performance testing to evaluate the degree of structural damage.
[0054] Comparative Examples 1-4
[0055] The catalytic layers used in Comparative Examples 1-4 correspond to the catalytic layers of Examples 1-4 that have not been immersed in H2O2 solution.
[0056] The catalyst layers prepared in Examples 1-4 were taped to the bottom of a glass container, and a H2O2 solution of a specified mass fraction was poured in for immersion. The catalyst layers before and after immersion were examined by optical microscopy to observe surface defects. The results are summarized in Table 1. The results show that the catalyst layers prepared with different slurry formulas had no surface defects before immersion in the H2O2 solution; however, after immersion, the mechanical strength of the catalyst layer prepared in Example 2 was poor, and the porous structure could not resist the gas erosion generated by the decomposition of the H2O2 solution. Therefore, this method can be used to simply conduct a preliminary screening of the mechanical strength and structural stability of the catalyst layer.
[0057] Table 1 Surface defects of the catalyst layer before and after immersion treatment in Examples 1-4
[0058] Compare Projects <![CDATA[Before soaking treatment with H2O2 solution]]> <![CDATA[After soaking and treating with H2O2 solution]]> Example 1 No surface defects Fewer surface defects Example 2 No surface defects Many surface defects Example 3 No surface defects Surface defects: No Example 4 No surface defects Fewer surface defects
[0059] The gas flushing phenomenon during the actual immersion process is shown in the attached Figure 1a and 1b , using the principle that highly active catalysts catalyze the decomposition of hydrogen peroxide into water and oxygen (2H2O2→2H2O+O2↑), a large number of bubbles are generated inside and on the surface of the catalyst layer. These bubbles will produce mechanical stress on the catalyst layer during the generation and desorption process, thereby simulating the bubble scouring effect during the operation of an actual electrolyzer, and are used for offline testing of the ability of the internal structure of the catalyst layer to resist bubble scouring.
[0060] Attached Figure 2a and 2b Figure 2 is an optical microscope photo of the catalyst layer of Example 2 before and after the immersion treatment. Figure 2a and 2b It can be clearly seen that the surface of the catalyst layer before immersion treatment is intact and has no defects, while there are many blank areas on the surface of the catalyst layer after immersion treatment, which is caused by the detachment of the catalyst. Figure 1a and 1b The strong gas scouring phenomenon displayed corresponds to the surface defects of the catalyst layer before and after the immersion treatment in Table 1, indicating that the catalyst layer prepared by this formula has poor structural strength and is not resistant to gas scouring.
[0061] The catalytic layers prepared in Examples 1-4 and Comparative Examples 1-4 were assembled into a single water electrolysis cell and subjected to a 240-hour steady-state durability test, followed by an electrolysis performance test.
[0062] The catalyst layers of Examples 1-4 after immersion treatment and the catalyst layers of Comparative Examples 1-4 without immersion treatment were prepared into active areas of 25 cm 2 The membrane electrode was used for electrolysis performance test. The specific performance values are shown in Table 2 and Table 3. The test conditions are: electrolysis temperature 70℃, anode water flow rate 1L / min, water resistivity greater than 10MΩ·cm. During the steady-state endurance test, the current density was 1A / cm 2 Keep for 240 hours.
[0063] Table 2 Electrolysis performance of membrane electrodes prepared by catalytic layers of Examples 1-4
[0064] Compare Projects <![CDATA[Before soaking treatment with H2O2 solution]]> <![CDATA[After soaking treatment with H2O2 solution]]> Example 1 <![CDATA[3.6A / cm 2 @2.0V]]> <![CDATA[3.3A / cm 2 @2.0V <!-- 4 -->]]> Example 2 <![CDATA[3.5A / cm 2 @2.0V]]> <![CDATA[2.3A / cm 2 @2.0V]]> Example 3 <![CDATA[3.8A / cm 2 @2.0V]]> <![CDATA[3.7A / cm 2 @2.0V]]> Example 4 <![CDATA[3.7A / cm 2 @2.0V]]> <![CDATA[3.3A / cm 2 @2.0V]]>
[0065] From the electrolysis performance data in Table 2, it can be seen that Example 2, in which many defects were washed out of the catalyst layer surface by gas after being immersed in H2O2 solution, also showed a great attenuation in electrolysis performance. At the electrolysis voltage of 2.0 V, the current density increased from 3.5 A / cm 2 Down to 2.3A / cm 2 ; Example 1, which has fewer surface defects and a firm catalyst layer structure, exhibits higher stability, with a current density from 3.6 A / cm 2 Only dropped to 3.3A / cm 2 The same phenomenon is also reflected in Examples 3 and 4. This can be explained from the gas erosion resistance of the catalyst layer. The catalyst layer with poor mechanical structure has obvious catalyst layer shedding and structural collapse on the surface, which will lead to the reduction of reactive active sites, increase of gas-liquid material transmission resistance and reduction of catalyst layer conductivity during the electrochemical reaction, which is further reflected in the reduction of current density under the same electrolysis voltage.
[0066] Table 3 Electrolysis performance of membrane electrodes prepared by catalytic layers of comparative examples 1-4
[0067] Compare Projects Before steady-state endurance test After steady-state endurance test Comparative Example 1 <![CDATA[3.6A / cm 2 @2.0V]]> <![CDATA[3.2A / cm 2 @2.0V]]> Comparative Example 2 <![CDATA[3.5A / cm 2 @2.0V]]> <![CDATA[2.2A / cm 2 @2.0V]]> Comparative Example 3 <![CDATA[3.8A / cm 2 @2.0V]]> <![CDATA[3.6A / cm 2 @2.0V]]> Comparative Example 4 <![CDATA[3.7A / cm 2 @2.0V]]> <![CDATA[3.1A / cm 2 @2.0V]]>
[0068] In order to verify the effectiveness of the method of evaluating the structure of the catalyst layer by immersion in H2O2 solution, the electrolytic performance before and after the steady-state durability test in Comparative Examples 1-4 is shown in Table 3. It can be found that the electrolytic performance after the 240-hour long-term test corresponds to the electrolytic performance after immersion in H2O2 solution. The catalyst layer that performed poorly in the examples still performed poorly in the comparative examples. Figure 3The comparison of electrolysis curves of Examples 1 and 2 and Comparative Examples 1 and 2 is shown in the figure, which reflects that the gas scouring effect of the anode oxygen production and the cathode hydrogen production experienced by the catalyst layer during the long-term steady-state test is similar to the effect of offline H2O2 solution decomposition to produce oxygen. Compared with the effect that requires long-term testing to obtain, the H2O2 solution immersion treatment method is much simpler and faster.
[0069] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. An off-line method for evaluating the gas scouring resistance of a catalyst layer, characterized in that: The following steps are involved: Step S1, mixing the catalyst, dispersant and ion exchange resin solution uniformly to form a catalyst slurry; Step S2, coating the catalyst slurry on the substrate, and drying at 60-80° C. to form a catalyst layer; Step S3, immersing the substrate coated with the catalytic layer in a hydrogen peroxide solution, controlling the immersion time, temperature and concentration of the hydrogen peroxide solution to simulate different degrees of bubble scouring, observing the generation and desorption process of bubbles on the surface of the catalytic layer, and recording the density and size of the bubbles; Step S4: After the test, rinse the surface of the catalyst layer with ultrapure water, let it stand and dry at room temperature, observe the integrity of the catalyst layer surface, and assemble the catalyst layer into a single water electrolysis cell for performance testing to evaluate the degree of structural damage.
2. The off-line method for evaluating the gas scouring resistance of the catalyst layer according to claim 1, characterized in that: In step S1, the catalyst includes a platinum-based catalyst and an iridium-based catalyst; The ion exchange resin solution is a cation exchange resin solution.
3. The off-line method for evaluating the gas scouring resistance of a catalyst layer according to claim 1, characterized in that: In step S2, the coating method includes one or more of spraying, blade coating, slot extrusion coating, inkjet printing and laser printing; The substrate comprises one of a polytetrafluoroethylene membrane, a polyimide membrane, a proton exchange membrane, an anion exchange membrane, carbon paper and titanium felt.
4. The off-line method for evaluating the gas scouring resistance of a catalyst layer according to claim 1, characterized in that: In step S3, the concentration of the hydrogen peroxide solution is 0.5-30%; The soaking time is 1-100h, and the soaking temperature is 20-80℃.
5. The off-line method for evaluating the gas scouring resistance of a catalyst layer according to claim 1, characterized in that: In step S4, the integrity of the catalyst layer surface is detected by using a scanning electron microscope or an optical microscope to observe whether there is damage including holes, cracks or peeling on the catalyst layer surface.
Citation Information
Patent Citations
Method for measuring mechanical strength of membrane electrode catalyst layer
CN114199757A
Cited By
Method and system for detecting gas scouring damage of electrolytic cell electrode catalytic layer
CN122709267A